The Mutations and Clinical Variability in Maternally Inherited Diabetes and Deafness: An Analysis of 161 Patients - Yang, Mengge; Xu, Lusi; Xu, Chunmei; Cui, Yuying; Jiang, Shan; Dong, Jianjun; Liao, Lin (Frontiers in Endocrinology, 2021)
Aims To investigate the clinical features and mitochondrial mutations for maternally inherited diabetes and deafness. Methods PubMed, Embase, Medline, Web of Science, the China National Knowledge Infrastructure, and Wanfang were searched with the following search terms: “Maternally inherited diabetes and deafness” OR “MIDD” OR “Mitochondrial diabetes”. The mutations and clinical features were analyzed. Correlation between the heteroplasmy levels of the m.3243A>G mutation in the peripheral blood and age at the onset of diabetes was conducted by Spearman test. The significance level was set as p < 0.05. Statistical analysis was performed using the Statistical Package for the Social Sciences version 26 for Windows. Results Totally 161 patients with 21 different mitochondrial mutations were enrolled. The most common mutation was the m.3243A>G mutation in 136 cases. Of 142 patients, 120 (84.51%) had family histories of diabetes or hearing loss. Hearing loss presented in 85.71% of the patients with mitochondrial mutations. Central nervous system diseases were found in 29.19%, myopathy in 22.98%, oculopathy in 23.60%, cardiac disease in 23.60%, and nephropathy in 13.66% of the patients. Forty-two of 101 (41.58%) patients were underweight. A significant negative correlation was found between the heteroplasmy levels of the m.3243A>G mutation in the peripheral blood and age at the onset of diabetes. Conclusions The young onset of diabetes with low or normal BMI, maternal inheritance, and presence of impairments of multiple systems should prompt a genetic testing in order to differentiate MIDD from other types of diabetes earlier.